Mental Health Evaluation in Community Pharmacies-A Cross-Sectional Study - Mónica Condinho; Isabel Ramalhinho; Catarina Vaz-Velho; Carlos Sinogas (MDPI AG, 2024)
Portugal has a high prevalence of anxiety and depression, and community pharmacists are well-placed to identify mental health problems and monitor their treatment. This study aimed to screen undiagnosed people for symptoms of anxiety and depression and to monitor these conditions in diagnosed patients. We conducted an observational, cross-sectional study of a sample of community pharmacy users. Anxiety and depression symptoms were assessed using the Generalised Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9). Altogether, 591 participants were enrolled between September 2020 and July 2021, 74.9% of whom were female. Of the 477 undiagnosed participants who completed the GAD-7, 87 (18.2%) had moderate or severe anxiety symptoms. Of the 485 participants who completed the PHQ-9, 59 (12.1%) had moderate or severe symptoms of depression. Of the 94 patients diagnosed with anxiety, 37 (39.4%) reported moderate to severe symptoms. Similarly, of the 97 patients with depression, almost half (49.5%) reported moderate to severe symptoms. Anxiety levels were lower among men and among those who reported not taking any medication (p < 0.001). Moderate or severe symptoms of depression were more common among women (p < 0.001), participants with lower education levels (p < 0.005), participants who live alone (p < 0.007), and those taking medication for insomnia (p < 0.001), pain (p < 0.001), anxiety (p < 0.001), and/or depression (p < 0.001). Screening for anxiety and depression revealed that a significant proportion of undiagnosed participants had clinically relevant symptoms of anxiety and depression. However, among participants diagnosed with anxiety and depression, between 40% and 50% were uncontrolled, respectively. These data highlight pharmacists' role in identifying customers at risk of anxiety and depression as well as the need for better monitoring of those already diagnosed.